A Study on the Effectiveness of Problem-based Learning in Legal Education in India. (January 2021) - Shalini, S.
Legal education in India aims at enabling learners to think critically and apply what they have learned. Problem-based learning (PBL) can be used as an effective tool to achieve this objective. This study was carried out to understand the effectiveness of this tool in legal education. A comparative analysis of the traditional method with PBL has shown that the latter leads to benefits in the form of better retention of knowledge and recall, improved problem-solving skill, better decision-making ability and development of lifelong-learning ability. This article discusses the methodology adopted and the results generated through application of the method in the taxation law course taught to undergraduate students of law.